Investigating Multiple Citizenship in International Relations: Rethinking Globalisation, Nation-States and Social Contract - Kang, Hyunji (UI Scholars Hub, 2018)
Multiple citizenship was once thought to signify disloyalty to the nation-state and threaten the sovereign international system, hence considered an aberration that should be limited. However, International Relations is in the process of reconceptualising its approaches and moving away from state-centrism so that it may better address the challenges of a transnationalising world. Examining the concept of multiple citizenship provides an opportunity to expand IR research agendas and transnationalise IR theory. Employing a multidisciplinary literature review, this article identifies the possible ways through which investigating multiple citizenship can contribute in advancing the discipline’s theorisations. Firstly, it contends that an analytical focus on multiple citizenship enriches IR theory by re-examining concepts which have not been adequately questioned in traditional IR and enabling deterritorialisation of the sovereign nation-state, de-conflation of the nation from the state, and reconsideration of the relationship between citizens and nation-states. Secondly, multiple citizenship can serve a base for considerations about globalisation and the future of the nation-state; it can also be used to obtain glimpses into issues, which may affect larger portions of the global population in the future. This article concludes by arguing for more serious probe to the concept of multiple citizenship in IR.